Ways of stimulating learning motivation among students in government schools according to several variables in Salfit Governorate - Palestine - Belbeisi, Mona AbdelQader (Journal of Educational and Psychological Sciences, 2020)
The current study aimed to identify the ways of raising the motivation of learning among tenth-grade students in public schools in Salfit governorate, according to the gender variable, the number of family members and the level of academic achievement. The researcher used the analytical descriptive approach to achieve the research aims, and the questionnaire was the research tool which applied on a sample of (83) students from the tenth-grade students in Salfit governorate. The results showed that there is no statistically significant relationship between each of the gender variable and the level of academic achievement, and the ways to raise the motivation of learning among the study sample, the results also showed that there is a strong positive relationship between the variable of the number of family members and the ways of raising the motivation of learning. Based on the results the research proposed a number of recommendations, the most important of which were: The necessity for pay attention when designing curricula and decisions to focus on addressing educational experiences that stimulate the learner's educational motivation and avoiding offering direct solutions that restrict the learner's thinking and make him anxious and tense.
Keywords: Learning Motivation; Educational Methods; Stimulate Motivation Methods; Motivation and Academic Achievement; Number of Family Members; Salfit Governorate